Hypoxia enhances interactions between Na+/H+ exchanger isoform 1 and actin filaments via ezrin in pulmonary vascular smooth muscle - Lade, Julie M.; Andrade, Manuella R.; Undem, Clark; Walker, Jasmine; Jiang, Haiyang; Yun, Xin; Shimoda, Larissa A. (Frontiers in Physiology, 2023)
Exposure to hypoxia, due to high altitude or chronic lung disease, leads to structural changes in the pulmonary vascular wall, including hyperplasia and migration of pulmonary arterial smooth muscle cells (PASMCs). Previous studies showed that hypoxia upregulates the expression of Na+/H+ exchanger isoform 1 (NHE1) and that inhibition or loss of NHE1 prevents hypoxia-induced PASMC migration and proliferation. The exact mechanism by which NHE1 controls PASMC function has not been fully delineated. In fibroblasts, NHE1 has been shown to act as a membrane anchor for actin filaments, via binding of the adaptor protein, ezrin. Thus, in this study, we tested the role of ezrin and NHE1/actin interactions in controlling PASMC function. Using rat PASMCs exposed to in vitro hypoxia (4% O2, 24 h) we found that hypoxic exposure increased phosphorylation (activation) of ezrin, and promoted interactions between NHE1, phosphorylated ezrin and smooth muscle specific α-actin (SMA) as measured via immunoprecipitation and co-localization. Overexpression of wild-type human NHE1 in the absence of hypoxia was sufficient to induce PASMC migration and proliferation, whereas inhibiting ezrin phosphorylation with NSC668394 suppressed NHE1/SMA co-localization and migration in hypoxic PASMCs. Finally, overexpressing a version of human NHE1 in which a single amino acid (glutamic acid) at residue 262 was mutated (E262I) prevented NHE1/ezrin/SMA interactions and was unable to increase PASMC migration and proliferation despite exhibiting normal Na+/H+ exchange activity. From these results, we conclude that hypoxic exposure increases ezrin phosphorylation in PASMCs, leading to enhanced ezrin/NHE1/SMA interaction. We further speculate that these interactions promote anchoring of the actin cytoskeleton to the membrane to facilitate the changes in cell movement and shape required for migration and proliferation.